EFFECTIVENESS OF BREASTFEEDING AND NON-NUTRITIVE SUCKING ON PAIN RELIEF IN INFANT IMMUNIZATION - Etri Probowati; Ariawan Soejoenoes; Sri Wahyuni M; Donny Kristanto Mulyantoro; Melyana Nurul Widyawati; Diyah Fatmasari (Belitung Raya Foundation, Indonesia, 2017)
Background: Immunization in infants is an action that can cause trauma due to injection of the immunization that can cause pain. Breastfeeding and non-nutritive sucking are considered non-pharmacologic strategies of pain management. Objective: This study aims to investigate the effectiveness of breastfeeding and non-nutritive sucking on pain relief in infant immunization. Methods: This was a quasi-experimental study with posttest only control group. This study was conducted on 26 October till 30 November 2016 at three Community Health Centers (Puskesmas), namely Puskesmas Cilacap Utara I, Puskesmas Cilacap Tengah, and Puskesmas Cilacap Selatan I. The population was infants aged 2-4 months who got immunization of DPT-HB-Hib 1. Samples were recruited using a consecutive sampling technique. There were 69 samples in this study, which were divided into three groups: 1) The group given a breastfeeding intervention (23 respondents), 2) The second group given a non-nutritive sucking intervention (23 respondents), and 3) The control group (23 respondents). Data were analyzed using ANOVA. Results: The average of pain response of the three groups was 2.74 in the breastfeeding group, 1.87 in the non-nutritive sucking group, and 3.26 in the control group. There was a significant difference between non-nutritive sucking and control group with p-value = 0.000, and also a significant difference between breastfeeding and non-nutritive sucking with p-value = 0.016. However, there was no difference between breastfeeding and control group with p-value = 0.142. Conclusion: Breastfeeding and non-nutritive sucking were effective in reducing pain during infant immunization. It is suggested that midwives could administer these interventions to reduce pain in infant immunization, and it could be applied as non-pharmacological strategy in pain management in the community health center in Indonesia.